Quality over quantity: How different dispersion qualities of minute amounts of nano-additives affect material properties in powder bed fusion of polyamide 12 - Sommereyns, Alexander; Gann, Stan; Schmidt, Jochen; Chehreh, Abootorab Baqerzadeh; Luddecke, Arne; Walther, Frank; Goekce, Bilal; Barcikowski, Stephan; Schmidt, Michael (Materials, 2021)
The great interest, within the fields of research and industry, in enhancing the range and functionality of polymer powders for laser powder bed fusion (LB-PBF-P) increases the need for material modifications. To exploit the full potential of the additivation method of feedstock powders with nanoparticles, the influence of nanoparticles on the LB-PBF process and the material behavior must be understood. In this study, the impact of the quantity and dispersion quality of carbon nanoparticles deposited on polyamide 12 particles is investigated using tensile and cubic specimens manufactured under the same process conditions. The nano-additives are added through dry coating and colloidal deposition. The specimens are analyzed by tensile testing, differential scanning calorimetry, polarized light and electron microscopy, X-ray diffraction, infrared spectroscopy, and micro-computed tomography. The results show that minute amounts (0.005 vol%) of highly dispersed carbon nanoparticles shift the mechanical properties to higher ductility at the expense of tensile strength. Despite changes in crystallinity due to nano-additives, the crystalline phases of polyamide 12 are retained. Layer bonding and part densities strongly depend on the quantity and dispersion quality of the nanoparticles. Nanoparticle loadings for CO2 laser-operated PBF show only minor changes in material properties, while the potential is greater at lower laser wavelengths.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Additively manufactured parts; Dispersion; Laser powder bed fusion; LB-PBF; Mechanical properties; Nanocomposites; Nanoparticles; Polyamide 12